A Non-Verbal Communication of Jack Mc Call on A Thousand Words Movie - Ismawati, Krisna; Ira Maisarah (UNIB Press, 2024)
Individuals interact through two components, namely verbal and nonverbal communication. The two components are inseparable. This article aims to examine the nonverbal cues exhibited by the American character, Jack Mc. Call, portrayed in the film